PENGARUH KOMUNIKASI INTERNAL, KOMPENSASI, LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI PADA CV.MEDINDA SEMARANG - Hastuti Purnaningrum; Ari Pradanawati; Reni Shinta Dewi (Jurnal Ilmu Administrasi Bisnis, 2012)
In achieving its objectives, CV.Medinda Semarang should consider factors that can affect the performance of the employees. Among them are internal communications, compensation, work environment, and motivation. The purpose of this study was to determine how much influence internal communications, compensation, work environment, employee performance motivation. The problem in this research is the company already provides internal communications, compensation, work environment that supports and provides motivation to employees to be more passion in work but are less target is reached. The results of the calculation is Y = (-2833) + 0,277 X1 + 0,164 X2 + 0,426 X3 + 0,222 Z that indicates that the work environment (X3) have a greater influence on performance (Y) when compared to internal communications (X1), compensation (X2) and Motivation (Z). It can be proved that the internal communications, compensation, work environment affects performance. The conclusion of this study is that there is influence between internal communications, compensation, work environment on performance through motivation at CV. Medinda Semarang. Suggestions for improving the performance of employees to improve the company's attention to aspects of internal communications, compensation, work environment, supported by a motivation to its employees to be more spirit in the work that will ultimately improve the performance of the employees.